A naturalistic epistemology selected papers - Kornblith, Hilary (Oxford University Press, 2015)
This volume draws together influential work by Hilary Kornblith on naturalistic epistemology. This approach sees epistemology not as conceptual analysis, but as an explanatory project constrained and informed by work in cognitive science. These essays expound and defend Kornblith's distinctive view of how we come to have knowledge of the world
Keywords: Knowledge, Theory of; Naturalism; Erkenntnistheorie; Erkenntnis; Naturalismus -- Philosophie; Aufsatzsammlung